2019
DOI: 10.3389/fendo.2019.00531
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Regulates Glucose Metabolism and Insulin Secretion in Rat Islet β Cells Through GPER and Akt/mTOR/GLUT2 Pathway

Abstract: Aims: To explore the molecular mechanism by which 17β-estradiol (estrogen 2, E2) regulates glucose transporter 2 (GLUT2) and insulin secretion in islet β cells through G protein-coupled estrogen receptor (GPER) via Akt/mTOR pathway. Methods: SPF-grade SD male rats were used to establish an in vivo type 2 diabetes model treated with E2. Rat insulinoma cells (INS-1) were cultured in normal or high glucose media with or without E2. Immunofluorescence doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 52 publications
1
32
0
1
Order By: Relevance
“…However, little is known about the mechanisms through which androgens are orexigenic [54,76]. ES increase insulin secretion and sensitivity, and suppress gluconeogenesis metabolism [77,78]. Pro-opiomelanocortin (POMC) neurons in the arcuate (ARC) nucleus of the hypothalamus, providing anorexigenic activity, express ERs.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the mechanisms through which androgens are orexigenic [54,76]. ES increase insulin secretion and sensitivity, and suppress gluconeogenesis metabolism [77,78]. Pro-opiomelanocortin (POMC) neurons in the arcuate (ARC) nucleus of the hypothalamus, providing anorexigenic activity, express ERs.…”
Section: Discussionmentioning
confidence: 99%
“…Two weeks after surgery, the OVX rats were began to receive different treatments. The doses of RJ and Es used in this study were selected according to previous studies (Ahmed, Khalaf, Moselhy, & Safwat, 2014;Bian, Bai, Gao, Li, & Zhao, 2019;Yang et al, 2012). The RJ groups were intragastrically administered RJ (RJL group, 150 mg kg -1 day -1 , RJM group, 300 mg kg -1 day -1 , RJH group, 450 mg kg -1 day -1 ) once per day for 8 weeks.…”
Section: Ovariectomy and Administrationmentioning
confidence: 99%
“…And the PI3K‐Akt pathway can regulate the expression of GLUT2 in liver tissue to regulate glucose and lipid metabolism. It has been found that the decreased expression of p‐Akt mRNA can also inhibit the expression of GLUT2 gene in patients with type 2 diabetes, and GLUT2 is mainly found in liver, kidney, and pancreas (Bian, Bai, Gao, Li, & Zhao, 2019). Our results showed that AUR can increase the protein levels of GLUT2 in liver.…”
Section: Discussionmentioning
confidence: 99%